Culture and sustainable development : cultural industries and the Caribbean Festival of Arts (CARIFESTA) - Brown, Hilary (2009)
Posits that mainstreaming culture in development thinking and changing the prevailing sustainable development paradigm to include culture is an essential feature of the sustainable development of SIDS. Reviews the Caribbean Festival and sets out elements of the new model and what it hopes to achieve.